Syukuran and Anniversary Celebration: Exposing Translation Non-Equivalency in Indonesian Novel - Ika Apriani Fata; Suci Aroh Syahiman (English LAnguage Study and TEaching, 2021)
Achieving equivalence is a significant issue in translation work. However, since one language is different in many aspects from other languages, non-equivalence is inevitable in the process of translation. Non-equivalence arises when the target language cannot provide equal meaning to the source-language text. By applying the framework proposed by Baker (2011), this research was designed using descriptive qualitative method to find out the cases of non-equivalence at word level in the translation of Negeri 5 Menara. The results showed 55 cases of non-equivalence at the word level were found. The cases were classified into seven out of eleven categories; (1) culture-specific concept with eight cases, (2) non-lexicalized source language concept with three cases, (3) different distinction in meaning with nine cases, (4) target language lacks superordinate with one case, (5) target language lacks hyponym with 15 cases, (6) differences in expressive meaning with eight cases, and (7) the use of loan word in the source text with 11 cases. Additionally, the findings also exposed 21 cases that were not categorized into Baker’s (2011) types of non-equivalences at the word level. It was suggested that future researches discuss the topic of non-equivalence words by applying other translation theories aside from Baker’s in order to cover the issue of uncategorized cases found in this study. It is important for translators to understand the contribution of equivalency in both source and target language so that the potential of misinterpretation was avoidable.